Clinical Spectrum, Diagnosis, and Management of TANGO2 Deficiency Disorder: A Comprehensive Review - Marcin Dołęga; Piotr Gacka; Olgierd Dróżdż; Joanna Gołda; Julia Mężyk; Aleksandra Snopkowska (Nicolaus Copernicus University in Toruń, 2024)
TANGO2 deficiency disorder is an autosomal recessive disease caused by biallelic pathogenic variants in the TANGO2 gene. First described in 2016, the disorder is characterized by acute metabolic crises, neurological dysfunctions, developmental delays, and intellectual disabilities. Laboratory findings indicate a mitochondrial fatty acid oxidation defect, with metabolic crises often triggered by stressors such as illness or fasting. The TANGO2 protein, implicated in lipid metabolism, membrane trafficking, and cellular homeostasis, is critical for maintaining lipid droplets, regulating phospholipid levels, and facilitating protein and lipid transport between cellular compartments. Symptoms of TANGO2 deficiency are diverse, including psychomotor delays, intellectual impairments, seizures, ataxia, and episodic neurological symptoms known as TANGO2 spells. Diagnosis involves genetic testing, with several pathogenic variants identified. During metabolic crises, patients may experience severe cardiac and metabolic disturbances. No curative treatment exists; management includes B-vitamin supplementation, antiepileptic drugs, and interventions for spasticity, dystonia, thyroid dysfunction, and arrhythmias. TANGO2 deficiency disorder can co-occur with DiGeorge syndrome, complicating diagnosis due to overlapping symptoms. Improved awareness and diagnostic strategies are crucial for effective management of this underrecognized condition.